RF conversion for power supply - Muhamad Fakrul Faiz Bin Sazali (School of Electrical System Engineering, University Malaysia Perlis, 2011)
A study on Radio frequency (RF) conversion to DC voltage has been undertaking. RF was generated from mobile phone of about 900MHz and harvested by a circuit called rectenna. The rectenna consists of antenna and rectifier. A simple helical antenna was used. The rectifier was just a voltage multiplier which converts the RF to DC voltage and at the same time its multiplied the voltage magnitude